PENGARUH KEPERCAYAAN DAN KERJASAMA TERHADAP KINERJA RANTAI PASOKAN DAN KEUNGGULAN BERSAING (STUDI PADA IKM OLAHAN RENDANG DI KOTA PAYAKUMBUH) - Dian, urnamasari; Samsir, Samsir; Iwan, Daulay Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to find out the influence of trust and cooperation on supply chain performance and competitive advantage on rendang processed IMIs in Payakumbuh City. The samples in this study include all rendang processed IKM in Payakumbuh City. The number of sample populations used is 41 respondents from IKM processed rendang. Primary data was collected with questionnaires as instruments to prove the results of the study, to test the hypothesis in this study is to use Structural Equation Modelling (SEM) analysis with the help of its analysis tool using WarpPLS Software. The results of this study show that there is a positive influence of trust on supply chain performance indicated by β = 0.343 p-value = 0.007 (≤0.05), and the cooperation positively affects supply chain performance indicated by β = 0.261 p-value = 0.035 (≤ 0.05). Supply chain performance positively affects competitive advantage indicated by β = 0.596 p-value = <0.001 (≤0.05).Keywords: Trust, Cooperation, Supply chain performance, Competitive advantage.